The Effect of Preparation Parameters in Thermal Decomposition of Ruthenium Dioxide Electrodes on Chlorine Electro‐Catalytic Activity. (28th April 2015) - Luu, Tran Le; Kim, Choonsoo; Kim, Jiye; Kim, Seonghwan; Yoon, Jeyong
<x xml:space="preserve">Abstract</x>